Disclosure of risk information in the explanatory notes of financial institutions in Brazil - Moura, Lucas Ferreira de; Matos, Eduardo Bona Safe de; Nasu, Vitor Hideo (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Objective: To map and analyze the level of risk disclosure presented in the financial statements of financial institutions operating in Brazil. Method: Checklist developed based on the guidelines of Resolution No. 4,557/2017 and the study by Basto and Marques (2024). The analysis focused on the explanatory notes included in the Consolidated Financial Statements (IFRS) of financial institutions classified in CMN’s S1 and S2 segments, covering the period from 2017 to 2023, with a total of 84 documents examined through content analysis. Results: The findings indicate that the most frequently disclosed risks were Market Risk (78%), Credit Risk (52%), and IRRBB (47%). An increase in disclosure levels was also observed during the first two years following the implementation of the Resolution, followed by relative stability and a decline over time. Variations in disclosure were noted across different periods and institutions, suggesting the absence of a consolidated standard for the sector. This highlights the need for progress in establishing clear criteria regarding which risk information is truly relevant to users. Contribution: As a social contribution, the results contribute to the debate on transparency in the banking market. As a practical and regulatory contribution, the findings may support regulatory authorities’ decisions regarding the inclusion or adjustment of minimum requirements for the disclosure of banking risks. Finally, as an academic and scientific contribution, the checklist for assessing the level of disclosure may be used in future research.